COMPARISON OF RED BLOOD CELL DISTRIBUTION WIDTH BETWEEN SIMPLE LESION AND MULTIPLE LESION OF CORONARY ARTERY IN ACUTE CORONARY SYNDROME PATIENTS - Ayuhati Siregar, Rahmad Isnanta & Zainal Safri (International Journal of Research Science and Management, 2019)
Introduction: Acute Coronary Syndrome (ACS) is a disease with the highest mortality. The main mechanism of coronary artery disease is atherosclerosis. Atherosclerosis is a multifactorial process that is influenced by various pathophysiological factors. One of these factors is inflammation. Recently, The red blood cell distribution width (RDW) has been investigated as an inflammatory marker in relation to cardiovascular disease. RDW is an easy, inexpensive and widely available examination in health facilities so that RDW can be used as a marker for assessing the severity of coronary artery lesions in patients with ACS. Aim: The aim of this study was to assess comparison of RDW values between simple lesion and multiple lesion of coronary artery in ACS patients. Methods: Cross-sectional study was conducted on 97 patients with ACS who underwent coronary angiography at Haji Adam Malik General Hospital Medan from July 2017 to July 2018. Patients were divided into two groups based on the number of coronary artery lesions, simple lesion group (consisting of 0 or 1 vessel disease) and multiple lesions group (consisting of 2 or 3 vessel diseases). Bivariate analysis with student’s t test was conducted to compared of RDW values between simple lesion and multiple lesion of coronary arteries in ACS patients. P values <0.05 were statistically significant. Result: A total of 97 consecutive patients with ACS, 48 patients (49.5%) with simple lesion and 49 patients (50.5%) with multiple lesion. The mean value of RDW in multiple lesion group was 13.4 ± 0.71%, while in multiple lesion was 12.17 ± 0.37% . There were significant diffrences in RDW values between simple lesion and multiple lesion group in ACS patients (p <0.001). Conclusion: RDW value in multiple lesion group was significantly higher compared to simple lesion group in ACS patients.